2008
DOI: 10.1007/s12011-008-8173-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Montmorillonite Superfine Composite on Growth Performance and Tissue Lead Level in Pigs

Abstract: A feeding trial was conducted to study the effect of montmorillonite superfine composite (MSC) on growth performance and tissue lead levels in pigs. Sixty barrows were randomly divided into two groups. They were fed the same basal diet supplemented with 0 or 0.5% MSC, respectively, for 100 days. Serum samples were collected and analyzed to study growth hormone secretion pattern. The mean lead concentration in selected tissues was analyzed. The results showed that average daily gain, average daily feed intake, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 13 publications
0
10
0
1
Order By: Relevance
“…Multiple studies have confirmed the decontaminating properties of clay minerals. They can bind: -aflatoxins (Phillips et al, 1987(Phillips et al, , 1988Lindemann et al, 1993;Schell et al, 1993a,b;Phillips et al, 2002;Abdel-Wahhab et al, 2002;Huebner and Phillips, 2003;Rizzi et al, 2003;Shi et al, 2005Shi et al, , 2007Maciel et al, 2007;Magnoli et al, 2008;Nguyen et al, 2008), -plant metabolites (Dominy et al, 2004), -heavy metals (Hassen et al, 2003;Katsumata et al, 2003;Lin et al, 2004;Xu et al, 2004;Yu et al, 2005Yu et al, , 2008Abbes et al, 2007), -toxins (Knezevich andTadic, 1994).…”
Section: Adsorption Capacity and Effects Of Clay Mineralsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have confirmed the decontaminating properties of clay minerals. They can bind: -aflatoxins (Phillips et al, 1987(Phillips et al, , 1988Lindemann et al, 1993;Schell et al, 1993a,b;Phillips et al, 2002;Abdel-Wahhab et al, 2002;Huebner and Phillips, 2003;Rizzi et al, 2003;Shi et al, 2005Shi et al, , 2007Maciel et al, 2007;Magnoli et al, 2008;Nguyen et al, 2008), -plant metabolites (Dominy et al, 2004), -heavy metals (Hassen et al, 2003;Katsumata et al, 2003;Lin et al, 2004;Xu et al, 2004;Yu et al, 2005Yu et al, , 2008Abbes et al, 2007), -toxins (Knezevich andTadic, 1994).…”
Section: Adsorption Capacity and Effects Of Clay Mineralsmentioning
confidence: 99%
“…Xia et al (2004) reported that Cu 2+ -enriched MMT significantly decreased the frequency of diarrhoea by up to 72 per cent and significantly increased the villus height and the villus height to crypt depth ratio in the jejunal mucosa by 19 and 37 per cent, respectively. Specific physical and chemical modifications -nanocomposites (Lin et al, 2004;Xu et al, 2004;Shi et al, 2005Shi et al, , 2007Yu et al, 2008), and complexes with organic materials (Xu et al, 1997;Herrera et al, 2000Herrera et al, , 2004Koh and Dixon, 2001), are characterized by much higher adsorptive abilities than other regular clay minerals. The effect of clay minerals can also be reinforced by the addition of other components such as charcoal or antioxidants (Bonna et al, 1991).…”
Section: Modified Forms Of Clay Mineralsmentioning
confidence: 99%
“…They show strong sorption properties, reduce the surface tension of the intestinal contents, enhance liver function emulsification of fats, have the ability to bind bacterial toxins and mycotoxins (Knezevich and Tadic, 1994;Magnoli et al, 2008;Trckova et al, 2009;Panichev et al, 2013;Schneider et al, 2017). They also cause a reduction in the emission of toxic gases from the litter (Schneider et al, 2017), limit the bioaccumulation of toxic metals (Yu et al, 2008) and supplement the animal diet with a range of macro-and micro-minerals like iron, magnesium or silicon (Al-Ani et al, 2006).…”
mentioning
confidence: 99%
“…Montmorillonite was found to be efficient in binding cadmium added to the basal diet at 0.5 % (Xu et al, 2004;Yu et al, 2009), showing less deposition in tissue and increased excretion. Concerning lead it was found that montmorillonite at an incorporation rate of 0.5 % reduced toxic effects in the liver (Yu et al, 2006) and decreased lead levels of tissues while improving performance parameters (Yu et al, 2005(Yu et al, , 2008. Grudnik et al (2005) found that 3 % bentonite in the diet reduced thallium concentration in whole eggs and thallium accumulation in muscle of laying hens.…”
Section: Interactions With Other Constituents Of the Dietmentioning
confidence: 99%